2020
DOI: 10.4038/cbj.v11i1.60
|View full text |Cite
|
Sign up to set email alerts
|

Indian Government Interventions in Micro, Small and Medium Enterprise Development: An Enterprise Life Cycle Perspective

Abstract: Development of Micro, Small and Medium Enterprise (MSME) sector is the most apt means of encashing the demographic dividend of India in promoting economic growth, employment generation and inclusive growth. In this endeavour, the Indian government periodically brings out appropriate support measures in the form of policies and programmes. Though many studies have been undertaken by various stakeholders in the past on myriad issues such as credit, marketing, skill development, sickness, export, technology infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…But recently, many studies confirmed that Government policy has a significant impact on the productivity of SMEs (Das and Rangarajan, 2020;Eniola and Entebang, 2015). Our study also confirms the same and reinforces the importance of government intervention on IEO and employee performance, as done by Socrates and Gopalakrishna (2020). The study revealed a favorable association between entrepreneurial values, business financing, management, market practices, and SME growth performance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…But recently, many studies confirmed that Government policy has a significant impact on the productivity of SMEs (Das and Rangarajan, 2020;Eniola and Entebang, 2015). Our study also confirms the same and reinforces the importance of government intervention on IEO and employee performance, as done by Socrates and Gopalakrishna (2020). The study revealed a favorable association between entrepreneurial values, business financing, management, market practices, and SME growth performance.…”
Section: Discussionsupporting
confidence: 87%
“…Regulatory policies, trade policies, labour market policies, regional development policies, social policies, and even gender policies of the government all have an impact on entrepreneurial activity (Ranjan and Panicker, 2020). This would rely on various factors, including the population's attitude towards entrepreneurship, labour force structure, the size and function of government, the prevalence of entrepreneurial activity, and the number of MSMEs in the country (Socrates and Gopalakrishna, 2020). To boost the number of new entrepreneurs and start-ups, the government must provide a supportive environment that encourages the appropriate individuals to become entrepreneurs and improves the quality of existing companies (Socrates and Gopalakrishna, 2020;Ranjan and Panicker, 2020).…”
Section: Government Intervention and Msme Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Daya saing UMKM dalam perekonomian global juga menjadi perhatian yang signifikan, dimana tantangan yang timbul akibat globalisasi berdampak pada UKM di berbagai negara (Singh et al, 2009). Selain itu, pengembangan UMKM sangat penting untuk mendorong pertumbuhan ekonomi, penciptaan lapangan kerja, dan pertumbuhan inklusif, khususnya di negara-negara seperti India (Socrates & Gopalakrishna, 2020).…”
Section: Pendahuluanunclassified